A2 Adenosine Receptors Mediate Whole-Body Insulin Sensitivity in a Prediabetes Animal Model: Primary Effects on Skeletal Muscle - Sacramento, Joana F.; Martins, Fátima O.; Rodrigues, Tiago; Matafome, Paulo; Ribeiro, Maria J.; Olea, Elena; Conde, Silvia V. (Frontiers in Endocrinology, 2020)
Epidemiological studies showed that chronic caffeine intake decreased the risk of type 2 diabetes. Previously, we described that chronic caffeine intake prevents and reverses insulin resistance induced by hypercaloric diets and ageing, in rats. Caffeine has several cellular mechanisms of action, being the antagonism of adenosine receptors the only attained with human coffee consumption. Here, we investigated the subtypes of adenosine receptors involved on the effects of chronic caffeine intake on insulin sensitivity and the mechanisms and sex differences behind this effect. Experiments were performed in male and female Wistar rats fed either a chow or high-sucrose (HSu) diet (35% of sucrose in drinking water) during 28 days, to induce insulin resistance. In the last 15 days of diet the animals were submitted to DPCPX (A1 antagonist, 0.4mg/kg), SCH58261 (A2A antagonist, 0.5mg/kg) or MRS1754 (A2B antagonist, 9.5µg/kg) administration. Insulin sensitivity, fasting glycaemia, blood pressure, catecholamines and fat depots were assessed. Expression of A1, A2A, A2B adenosine receptors and protein involved in insulin signaling pathways were evaluated in the liver, skeletal muscle and visceral adipose tissue. UCP1 expression was measured in adipose tissue. Paradoxically, SCH58261 and MRS1754 decreased insulin sensitivity in control animals, whereas they both improved insulin response in HSu diet animals. DPCPX did not alter significantly insulin sensitivity in control or HSu animals, but reversed the increase in total and visceral fat induced by the HSu diet. In skeletal muscle, A1, A2A and A2B adenosine receptor expression were increased in HSu group, an effect that was restored by SCH58261 and MRS1754. In the liver, A1, A2A expression was increased in HSu group, while A2B expression was decreased, being this last effect reversed by administration of MRS1754. In adipose tissue, A1 and A2A block upregulated the expression of these receptors. A2 adenosine antagonists restored impaired insulin signaling in the skeletal muscle of HSu rats, but did not affect liver or adipose insulin signaling. Our results show that adenosine receptors exert opposite effects on insulin sensitivity, in control and insulin resistant states and strongly suggest that A2 adenosine receptors in the skeletal muscle are majors responsible for whole-body insulin sensitivity.